(untitled) (Journal of Ideas in Health, 2025)
Background: Intrauterine contraceptive device (IUCD) migration into the urinary bladder is a rare complication that may cause recurrent urinary tract infections, hematuria, abdominal pain, and bladder stone formation. Case presentation: A 47-year-old woman presented to the urology clinic at Life Hospital in Kalar, Iraq, in September 2025 with chronic intermittent lower abdominal pain, hematuria, and recurrent UTIs. Her medical history was unremarkable, and she had a copper-T IUCD inserted in 2005. She reported mild post-insertion bleeding and later experienced an early miscarriage and a term home delivery. Examination revealed left iliac fossa tenderness and a positive urine culture for E. coli. Imaging showed a 22 mm intravesical stone attached to a migrated IUCD. CT confirmed one T-limb in the bladder forming a stone, with the other limb penetrating the abdominal wall. Failed cystoscopic and laparoscopic attempts led to open surgery. The IUCD and stone were successfully removed, and the bladder was repaired. Recovery was uneventful, with catheter removal following a clear cystogram. Conclusion: Early recognition and prompt surgical removal of migrated IUCDs are crucial to prevent chronic infection, adhesion, and bladder wall damage.